30. BACTERIAL CHARACTERISTICS AND ANTIBIOLOGY RESULT IN ACUTE SINUSITIS IN CHILDREN AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Identify some bacteria causing acute rhinosinusitis and the antibiotic sensitivity level of bacteria in acute rhinosinusitis in children at Nhi An Obstetrics and Children’s Hospital from March 2022 to September/ 2022.Research subjects and methods: Cross-sectional descriptive study conducted on 42 children with acute infectious rhinosinusitis at the respiratory department of Nghe An Obstetrics and Children’s Hospital through clinical examination, combined with ENT endoscopy used a 2.7mm diameter Karlstorz endoscope and testing to identify pathogenic bacteria.Results: Our results showed that three most common bacterial species are: Streptococcus Pneumoniae, Haemophilus Influenzae, and Moraxella Catarrhalis with rates of 65,2%; 17,4%, and 13,0% respectively. Bacteria species are susceptible from 75-100% to the antibiotic Amoxicillin + clavulanic acid. The antibiotics cefuroxime and Trimethoprim + Sulfamethoxazole have low sensitivity in most bacterial groups. Antibiotic groups are rarely prescribed for children, especially Ciprofloxacin, Moxifloxacin and Levofloxacin are highly susceptible to all common bacterial groups. Culture identification of bacteria in acute sinusitis in children helps clinicians guide the use of appropriate resistance for treatment. Research with larger samples is needed to comprehensively understand the causative bacteria and choose the most appropriate antibiotic treatment.Conclusion: Common pathogenic bacteria in acute sinusitis in children are Streptococcus Pneumoniae, Heamophilus Influenzae and Moraxella Catarrhalis and all have quite high sensitivity from 75-100% to the antibiotics Amoxcillin + Clavulanic Acid. Third generation Cephalosporin antibiotics such as Ceftriaxone and Cefotaxime and other rarely used β-lactam antibiotics such as Cefepime, Ceftazidime, Imipenem, Meropenem are highly sensitive to common bacteria with rates ranging from 66.7%-100%. %. Clinical examination combined with bacterial identification tests and antibiograms is an effective method in treatment.
Keywords: Children, acute sinusitis, bacteria, antibiotics.